Biomass and morphology of fine roots of sugi (Cryptomeria japonica) after 3 years of nitrogen fertilization - Noguchi, Kyotaro; Nagakura, Junko; Kaneko, Shinji (Frontiers in Plant Science, 2013)
Increasing nitrogen (N) deposition may affect carbon and nutrient dynamics in forest ecosystems. To better understand the effects of N deposition, we need to improve our knowledge of N effects on fine roots (roots < 2 mm in diameter), as they are a key factor in carbon and nutrient dynamics. In this study, we fertilized 1 × 2 m plots in a sugi (Cryptomeria japonica) stand (336 kg ha-1 y-1) for three years and evaluated the responses of the fine roots to high N load. After fertilization, the concentration of NO3-N in the soil of N-fertilized (NF) plots was 5-times as large as that in the control plots and the effect was more remarkable in the subsurface soil than in the surface soil. The biomass of fine roots < 2 mm in diameter appeared to be greater in the NF plots (88 ± 19 g m-2) than in the control plots (56 ± 14 g m-2), but this difference was not statistically significant. In both plots, 76% of the biomass was accounted for by fine roots that were < 1 mm in diameter. In the surface soil, the specific root length (SRL) of fine roots < 1 mm in diameter was significantly greater, and the diameter of those fine roots was marginally smaller, in the NF plots than in the control plots. In addition, the concentration of N in fine roots < 1 mm in diameter was marginally greater in the NF plots than in the control plots. There may have been increased production of thinner fine roots or increased root branching in the NF plots. This study suggests that, in general, high N load is likely to have positive effects on sugi in terms of fine root characteristics and the effects on fine-root morphology are more evident than the effects on fine-root biomass.